Facilitating the participation of civil society in regional planning: Implementing quadruple helix model in Finnish regions. (January 2022) - Roman, Mona; Fellnhofer, Katharina
Abstract: The engagement of a wide range of stakeholders has become a key element in regional planning, particularly in the development of regional research and innovation strategies for smart specialization (RIS3) in Europe. The quadruple helix model from the literature on regional innovation systems has been raised on the forefront of RIS3. This comes in spite of the fact that the literature surrounding the quadruple helix model (i.e., the collaboration among the university, industry, government, and civil society) is still in its infancy compared to the well-established triple helix model. Our paper addresses this gap and explores how regional authorities can facilitate the participation of the fourth helix (civil society) and ensure democracy of the participatory policy process. We adopted a grounded theory approach and collected primary data through interviews with regional authorities in Finland. Based on 28 interviews from all 18 Finnish mainland regions, we identified three mechanisms for facilitating the participation of civil society: information exchange, feedback, and co-creation. For policy-makers, our paper provides recommendations on how to overcome impediments in the engagement of civil society in regional planning. Highlights: Information exchange, feedback and co-creation facilitate the participation of the civil society in regional planning. Information exchange improves public awareness and enables learning and contribution of civil society in regional planning. Regional authorities seek feedback for planning through surveys and regular meetings with civil society organizations. Co-creation involves quadruple helix interaction and collaboration facilitated by regional authorities. Regional authorities should provide transparent rules and guidance to support the participation of civil society.